2021
DOI: 10.4252/wjsc.v13.i7.914
|View full text |Cite
|
Sign up to set email alerts
|

Current advances of stem cell-based therapy for kidney diseases

Abstract: Kidney diseases are a prevalent health problem around the world. Multidrug therapy used in the current routine treatment for kidney diseases can only delay disease progression. None of these drugs or treatments can reverse the progression to an end-stage of the disease. Therefore, it is crucial to explore novel therapeutics to improve patients’ quality of life and possibly cure, reverse, or alleviate the kidney disease. Stem cells have promising potentials as a form of regenerative medicine for kidney diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 177 publications
0
13
0
Order By: Relevance
“…About a third of the studies investigated the preventive benefits of such therapies, while half of the studies focused on their therapeutic benefits. For instance, in AKI animal models, mesenchymal stem cells improved renal function [55][56][57]. Even though the specific mechanisms of action are still under investigation, these cells helped reduce renal fibrosis, improve remodeling, and promote neoangiogenesis [58].…”
Section: Cell and Organoid Transplantationmentioning
confidence: 99%
“…About a third of the studies investigated the preventive benefits of such therapies, while half of the studies focused on their therapeutic benefits. For instance, in AKI animal models, mesenchymal stem cells improved renal function [55][56][57]. Even though the specific mechanisms of action are still under investigation, these cells helped reduce renal fibrosis, improve remodeling, and promote neoangiogenesis [58].…”
Section: Cell and Organoid Transplantationmentioning
confidence: 99%
“…Over the last few decades, many studies have shown that transplanting stem cells to patients with kidney disease improves their kidney function (11). Among all stem cell types, mesenchymal stem cells (MSCs) have been identified as one of the most effective cell types for inducing kidney regeneration due to their ease of isolation and expansion and lack of teratoma risk, immunosuppressive properties, and absence of ethical problems (12,13).…”
Section: Contextmentioning
confidence: 99%
“…Complications of CKD have a major impact on the quality of life of patients and can increase the risk of mortality ( Webster et al, 2017 ). According to Global Burden Assessment Report, the number of people dying of CKD has increased in recent years ( Xie et al, 2018 ; Wong, 2021 ). The prevalence of CKD is rising as the incidences of the main risk factors for CKD, including DM and hypertension, are sharply increasing, leading to a rising prevalence of CKD.…”
Section: Introductionmentioning
confidence: 99%